Tacitus and the Tacitean Tradition - Luce, Torrey James (Princeton Legacy Library, 2014)
Pages:1 to 25 -- Pages:26 to 50 -- Pages:51 to 75 -- Pages:76 to 100 -- Pages:101 to 125 -- Pages:126 to 150 -- Pages:151 to 175 -- Pages:176 to 200 -- Pages:201 to 225.